Eyewitness History of World War II (Vol.4) : Victory - Rothberg, Abraham (New York Bantam Books, 1962)
Volume 4: Victory - Eyewitness History of World War 2 the Total Experience in Words and Photographs from D-Day in Europe to the Unconditional Surrender Of Japan covers the last stages of the war in both the Eurppean and Pacific theaters.
Includes Illusrations
Keywords: World War (1939-1945)